2019
DOI: 10.5812/jjhs.86427
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Study of Drug Use, Depression, and Anxiety Reduction and Quality of Life in Addicts on Methadone Maintenance Therapy

Abstract: Background:This study aimed to evaluate reduced drug consumption, risky behaviors, depression, and anxiety and improved quality of life in addicts on methadone maintenance therapy (MMT) at baseline and six months after therapy. Methods: In this descriptive cross-sectional study, 275 addicts were selected by a random sampling method in 2017. The data collection tools consisted of four questionnaires including a demographic information questionnaire, the Beck depression inventory questionnaire, WHOQOL-26, and Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our study showed anxiety in the methadone group is 27% (OR = 0.73; 95% CI 0.61-0.88) lower than the buprenorphine. This finding was consistent with some studies conducted in this field [22][23][24]. For example, the study of Dehkordi et al, with the aim of investigating the effect of methadone on depression, anxiety, and quality of life of addicts in Iran, indicates a reduction in situational anxiety after methadone administration [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed anxiety in the methadone group is 27% (OR = 0.73; 95% CI 0.61-0.88) lower than the buprenorphine. This finding was consistent with some studies conducted in this field [22][23][24]. For example, the study of Dehkordi et al, with the aim of investigating the effect of methadone on depression, anxiety, and quality of life of addicts in Iran, indicates a reduction in situational anxiety after methadone administration [24].…”
Section: Discussionsupporting
confidence: 90%
“…For example, the study of Dehkordi et al, with the aim of investigating the effect of methadone on depression, anxiety, and quality of life of addicts in Iran, indicates a reduction in situational anxiety after methadone administration [24]. The study by Almasi et al Also showed that the mean score of anxiety decreased significantly after methadone administration (39.40 vs. 20.41) [23]. However, compared to some other studies, this alignment was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The health-related quality of life (HRQOL) can be used to predict the effects of diseases, damages, and infirmities, as well as to assess mental health (8). An individual's HRQOL is determined by various factors, including their physical health, mental health, level of independence, social relationships, personal beliefs, and relationship with their environment (9,10). Parent-child interaction is another factor that affects the HRQOL of parents of children with specific learning disabilities.…”
Section: Introductionmentioning
confidence: 99%